Gender-Based Language Variation in Everyday Conversation: Dell Hymess's Theory - Imroatul Munawaroh; Mariam Ulfa (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyze language variations based on gender in everyday conversation, focusing on speaking style (key) and conversation topics (act sequence) based on Dell Hymes' theory. This research is based on the urgency of understanding differences in communication patterns between genders as part of the dynamics of social interaction in society. This study uses a descriptive qualitative approach with the listening and speaking methods. This approach is used because the research data is in the form of oral speech that contains meaning, is influenced by social context, and shows variations in language use that cannot be expressed in numerical form. The listening method is used to obtain data by listening to the use of language conveyed by the speaker. Meanwhile, the speaking method is used to collect linguistic data through direct communication between researchers and informants in the form of conversations or dialogues. Data collection techniques include listening and speaking, recording, and note-taking. Data analysis is carried out through the techniques of selecting certain elements, linguistic analysis, qualitative analysis, and data interpretation. The results of the study indicate that there are differences in language variations between men and women. Men tend to use assertive, rational, and efficient language, while women are more expressive and collaborative. In the parent group, fathers used practical and solution-oriented language, while mothers were more communicative and expressive. These findings suggest that gender influences speaking style and topic choice in everyday interactions.